IMPROVING MOTIVATION, LEARNING EFFICIENCY UTILIZING RINFO AND IME (A CASE STUDY OF HIGHER EDUCATION RAHARJA) - Sudaryono Sudaryono; Untung Rahardja; Bayu Pramono (ICIT Journal, 2017)
Student learning motivation is one aspect to obtain good learning outcomes. With good learning outcomes, the application of the knowledge gained will be useful for students. the current application of the system of teaching in an evening class Raharja university been computerized for the submission of learned, but it had not been optimal and efficient because of teaching materials that can not be obtained from anywhere and at anytime as well as teaching and learning activities and discussions carried out only in the class so that students tend to be saturated and show the emotional symptoms such as lack of zeal in carrying out lectures, so that suggests a self learning disabilities in students. learning difficulties allegedly closely associated with the motivation to learn owned. Thus the need for a new learning method is applied so that students can termotiviasi and efficiency in learning. In this study the application of the system of learning that will be used is to utilize Rinfo in the adoption of Gmail and iMe in the adoption of Wordpress so that lessons learned are easily digested and fun and will make students more motivated to learn determination of students to be more active. Liveliness characterized by the activity of the post and comment on the iMe so that it can be measured with a dashboard on the front page of an iMe Class which will be a medium for decision support lecturers to give the value of the assignment to students. for the research method used is qualitative, to examine the population or sample data collection using research instruments, analysis of quantitative data which will then be tested for validity and reliability so that we can conclude effect of the use Rinfo and iMe in increasing motivation and efficiency of learning in students. Keywords: Motivation, Rinfo and iMe, Learning Outcome.